Analisa Perencanaan Dan Pengendalian Persediaan Bahan Baku Kasur Busa Dengan Metode Eoq (Economic Order Quantity) Pada Pt. Kurnia Persada Mitra Mandiri - Sinta Sinta; Maulan Irwandi; Muhammad Hamdan Sayadi (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to analyze the planning and control of raw material inventory at PT. Kurnia Persada Mitra Mandiri. The analysis was performed using the EOQ (Economic Order Quantity) method. This analysis technique consists of reviewing the reorder point, safety stock, and total annual inventory cost. The results show that by using the EOQ method, the company can find out how many times raw materials are purchased and in the quantity how many times raw material purchases are made, know how much minimum stock is needed to be on guard, determine the time to reorder raw materials, and know the cost. The results showed that by using the EOQ method the company could generate more optimal profits compared to conventional methods. Furthermore, the research results also show that with the application of EOQ, companies can make savings on raw material inventory costs, namely in 2018 amounting to IDR 19.092.034 and in 2019 of IDR 21.053.480. In the end, this research is expected to provide insights for companies to use the EOQ method sustainably so that the process of planning and controlling raw materials is better.